Fungsi-Fungsi Administrasi dan Manajemen Pendidikan - Abdullah Muis Kasim; Lisnawati Lisnawati; Maria Yuni Yanti Tia; Maryono Maryono; Maria W. Verlina Nona; Maria Ranciana Bhae; Maria Nona An (Educational Journal, 2026)
Educational administration and management are essential components of educational governance that ensure all educational resources are effectively and efficiently organized to achieve educational goals. This article aims to examine the concepts of educational administration and management, their objectives, principal functions, implementation in educational institutions, and the supporting and inhibiting factors affecting their application. The study employed a library research method by reviewing and analyzing relevant scholarly literature, including books, journal articles, and educational policy documents. The findings indicate that educational administration encompasses a broader scope than educational management, while educational management primarily focuses on implementing the POAC functions: Planning, Organizing, Actuating, and Controlling. The effective implementation of these functions contributes to improved institutional management through systematic planning, task distribution, instructional implementation, and continuous supervision and evaluation. Furthermore, successful educational management is influenced by the quality of human resources, leadership, educational facilities, government support, and the effective utilization of technology. Therefore, the consistent application of management functions is essential for improving the quality of education and ensuring the achievement of educational objectives